Preparation of zinc oxide nanoparticles by laser ablation in various liquid media - Jorfi, Raheleh (2014)
A big challenge in the synthesis of nanoparticles (NPs) is particle agglomeration. This tendency can be inhibited by stabilization of NPs and therefore much effort by researchers has been undertaken to use different liquid media as stabilizers. In the present study we have investigated the fabrication of zinc oxide nanoparticles (ZnO-NPs) using Laser Ablation (LA) technique. The first objective is studying the effect of laser parameters on fabrication of ZnO-NPs and secondly investigating the medium effect on optical properties and size of ZnO-NPs. The LA to ZnO plate was carried out in various media such as distilled water, polyvinyl acetate aqueous solution, ethylene glycol, and rice bran oil, and then characterized by UV-vis, photoluminescence (PL), FT-IR spectroscopy, and TEM microscopy. It was revealed the generation of NPs by LA in various liquid media was higher in comparison with in distilled water. The increased NPs generation is attributable to solvent plasma confinement toward the plate. In addition, at longer ablation duration the size decrease of NPs was remarkable. The UV-vis absorption spectra of the ZnO-NPs are monitored to characterize the particle growth because the onset of absorption is associated with the particle size. It is observed that average NPs size decreases with the increase of ablation time. The decrement can be explained by the way that at longer ablation time, there is an increment of produced NPs from the plate since more interactions occurred between target and laser light. NPs with different sizes demonstrate different optical properties; when the particle diameter decreased there is a blue-shifted in absorption spectra. It can be observed that increasing repetition rate lead to larger particle diameter. This size increment is confirmed by the red-shifted absorption spectra. We analyzed PL spectra to see the emission spectra of fabricated NPs. Both the absorption and emission band positions are dependent on the polarity of the medium; in the medium the PL spectrum is much more sensitive than the absorption spectrum. PL spectra of all fabricated ZnO-NPs show two emission peaks; the first one is sharp and narrow UV emission corresponds to excitonic emission and the second one is broad blue-green emission commonly referred to a deep-level or a trap-state emission attributed to the singly ionized oxygen vacancy of ZnO. TEM images also show the morphology of the ZnO-NPs as they were all spherical. The produced ZnO-NPs in rice bran oil were well dispersed; those fabricated in polyvinyl acetate were more stable than other liquid media. Ethylene glycol has ability to prevent agglomeration of NPs. The average diameter of the obtained ZnO-NPs in distilled water was large; 27.12 nm, on the other hand rice bran oil leads to fabricate fine ones; 14.17 nm.